Mutu Pelayanan Voluntary Counseling and Testing (VCT) di Klinik VCT Puskesmas Puger dari Perspektif Provider - Indah Ernawati; Christyana Sandra; Yennike Tri Herawati (Pustaka Kesehatan, 2019)
Voluntary Counseling and Testing (VCT) is an entry point to help everyone in utilizing services related to HIV-AIDS prevention, care, support and treatment. Puger Primary Health Care is a primary health care located in the work area with the highest number of HIV-AIDS sufferers in Jember Regency, experiencing a decrease in client visits, and there are some management services that are still not in accordance with VCT guidelines. This study aimed to describe the quality of VCT services at the VCT Clinic Puger Primary Health Care from the perspective of provider. This study was descriptive study using questionnaire, documentation study, and observation. The study respondents were 7 VCT clinic officers. The results indicated that in input parameter showed a lack of human resources, insufficient funding, lack of availability and material conditions that meet the VCT guidelines. In planning indicators related to the human resources, improvements of infrastructure facilities had not been written in the POA, the job description was sufficient based on duties and competences of staff and there were coordination, supervision and evaluation. In the dimensions of technical competence, access to services, efficiency, human relations, continuity and safety of VCT clinics in good categories, but sufficient and less categories for dimensions of effectiveness and comfort dimensions.